Qualitative Test of Rhodamine B and Methanyl Yellow Using the Spot test Method on Packaged Beverage at The Center for Drug and Food Control Denpasar - Yola Monalisa R Simamora; Gusti Ayu Kadek Diah Puspawati (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
Rhodamine B and Methanyl Yellow are synthetic dyes that are widely used in the textile and paper industries. Rhodamine B is a synthetic dye that produces a red color and Methanyl Yellow is a synthetic dye that produces a yellow color. Based on the decision of the Ministry of Health (Permenkes) No. 239/Menkes/Per/V/85 Rhodamin B and Methanyl Yellow are designated as substances whose use is prohibited in food products. The use of this dye if consumed can cause irritation to the respiratory tract, skin, eyes, digestive tract, the danger of liver cancer, and as a tumor-triggering agent. So based on the above problems it is necessary to identify Rhodamin B and Methanyl Yellow in food products. The method that has been developed and used in the identification of Rhodamine B and Methanyl Yellow is using a qualitative descriptive analysis technique with the spot test method. This research was conducted by direct observation to the field to find indications for the use of Rhodamine B and Methanol Yellow to be tested. This study aims to determine whether or not the use of Rhodamine B and Methanyl Yellow in packaged beverage products at the Denpasar Food and Drug Supervisory Agency. The research samples were 2 packaged drinks which had striking red and striking yellow colors. The results showed that none of the samples contained Rhodamine B and Methanol Yellow synthetic dyes.